Syphilis Testing among Men Who Have Had Rectal Gonorrhea and Chlamydia Tests, United States - Guoyu Tao; Thomas A. Peterman; Thomas L. Gift; Melinda B. Nye
The Centers for Disease Control and Prevention (CDC) recommends syphilis screening at least annually for sexually active men who have sex with men (MSM). The objective of this study is to assess the frequency of MSM testing for syphilis and how syphilis test results compared with results of rectal gonorrhea and chlamydia tests. In collaboration with a large US commercial laboratory, we identified men aged 15-60 years who had rectal chlamydia or gonorrhea tests during 09/01/2013-09/30/2015 as presumed MSM. We classified MSM as having current or past syphilis if during the study period they had (1) either a reactive qualitative non-treponemal test or at least a 1:1 quantitative non-treponemal test, and (2) they had a reactive treponemal test. Of 52,771 MSM, 14.3% had no syphilis testing, 4.8% had only treponemal testing (37.8% were reactive), 63.2% had only non-treponemal testing (2.0% were reactive), and 17.7% had both non-treponemal and treponemal testing (86.6% had current or past syphilis). Of those MSM who had reactive qualitative non-treponemal tests, at least 90% had no quantitative non-treponemal tests. Current or past syphilis was more common among MSM with positive rectal gonorrhea or chlamydia tests (24.1%) than MSM with negative rectal gonorrhea and chlamydia tests (13.0%, p < 0.005). Of MSM with any syphilis testing during 09/01/2013-09/30/2014, 64.8% also had annual repeat testing. Syphilis testing in general and repeat syphilis testing were frequent but suboptimal among MSM. It is important to continually monitor syphilis for MSM, especially for those MSM who had rectal chlamydia or gonorrhea infection.